Transmissibility of Mycobacterium pinnipedii in a murine model - Marfil, María Jimena; Blanco, Federico Carlos; Colombatti Olivieri, María Alejandra; Eirin, María Emilia; Zumárraga, Martín José (Frontiers in Cellular and Infection Microbiology, 2024)
The causative agent of tuberculosis in pinnipeds is Mycobacterium pinnipedii, a member of the Mycobacterium tuberculosis complex (MTC). Natural hosts are pinnipeds; however, other non-marine mammals, including humans, can be infected as well. The transmissibility of a pathogen is related to its virulence. The transmission of a M. pinnipedii (1856) strain was investigated in a murine model and compared to the transmissibility of two Mycobacterium bovis strains (534 and 04-303) with different reported virulence. Non-inoculated mice (sentinels) were cohoused with the intratracheally-inoculated mice. Detailed mouse inspection in search of visible tuberculosis lesions in lungs and spleens, as well as bacilli viability at days 30, 60 and 90 post inoculation (dpi), were assayed. One hundred percent transmissibility was recorded at 30 dpi in the sentinel mice cohoused with the inoculated mice belonging to the M. pinnipedii and M. bovis 04-303 groups as evidenced by the recoverying of viable M. pinnipedii and M. bovis from sentinel mice lungs. Mice inoculated with M. pinnipedii (1856) and M. bovis (534) survived until euthanized, whereas five of the M. bovis 04-303 inoculated mice died at 17 dpi. This study constitutes the first report of transmissibility of a M. pinnipedii strain in mice and confirms the utility of this experimental model to study virulence features such as transmission of poorly characterized MTC species.